Ferramentas de monitoramento wearable durante a gestação: a proposta de uma rede baseada em valor - Silva, Allisson Jonathan Marques da (2022)
The need for medical care has been growing faster than the supply, every day technologies that can optimize the supply of medical care are more necessary, when we talk about gestational health this topic gains even more space. Monitoring the health of pregnant women, especially those with a high-risk pregnancy, is one of the main ways to reduce gestational mortality. One of the technologies that can help in this process are wearable monitoring devices, as they can allow continuous monitoring during pregnancy. There are many advantages associated with using this technology, as well as many barriers. The development of the tool is not the only challenge, its acceptance by patients and health professionals is also an obstacle to be overcome. Getting them to accept, understand and use these technologies is an essential factor for successful patient monitoring. Thus, this research aims to understand what are the aspects that motivate the use of these monitoring wearables by both patients and health professionals. For this purpose, the Value-Focused Thinking method was used to build a network of values, providing a framework with 26 Objectives Means to achieve 3 Objectives and End that consist of Maximizing the Quality of Prenatal Care, Minimizing Deaths and Minimizing Health System Costs. This framework can be used by health system stakeholders, whether researchers, technology developers, health professionals, health policymakers, medical insurance, among others.